Efficacy and Safety of Bevacizumab Biosimilars Compared With Reference Biologics in Advanced Non-small Cell Lung Cancer or Metastatic Colorectal Cancer Patients: A Network Meta-Analysis - Xinyi Xu; Xinyi Xu; Shengzhao Zhang; Ting Xu; Ting Xu; Mei Zhan; Chen Chen; Chen Chen; Chenyu Zhang; Chenyu Zhang (Frontiers Media S.A., 2022)
Background: Bevacizumab biosimilars are slowly making their way into cancer treatment, but the data on their efficacy and safety in cancer patients are still poor. We systematically summarized the current evidence for the efficacy and safety of bevacizumab biosimilars in patients with advanced non-small cell lung cancer (NSCLC) or metastatic colorectal cancer (CRC).Methods: This review searched CNKI, VIP, PubMed, Medline (Ovid), Embase, and Cochrane Library (Ovid) for randomized controlled trials of bevacizumab biosimilars treated in adults with advanced NSCLC or metastatic CRC. A pairwise meta-analysis and a Bayesian network meta-analysis based on the random-effect model were performed to summarize the evidence. We rated the certainty of evidence according to the Grading of Recommendations Assessment, Development, and Evaluation framework.Results: Ten eligible trials with a total of 5526 patients were included. Seven trials (n = 4581) were for the NSCLC population, while three trials (n = 945) were for patients with CRC. According to the pairwise meta-analysis, the efficacy (objective response rate: risk ratio (RR) 0.98 [0.92-1.04], p = 0.45; progression-free survival: hazard ratio (HR) 1.01 [0.92-1.10], p = 0.85; and overall survival: HR 1.06 [0.94-1.19], p = 0.35) and safety (incidence of grade 3-5 adverse events: odds ratio (OR) 1.03 [0.91-1.16], p = 0.65) of bevacizumab biosimilars performed no significant difference with reference biologics in patients with NSCLC as well as metastatic CRC patients (objective response rate: RR 0.97 [0.87-1.09], p = 0.60; overall survival: HR 0.94 [0.70-1.25], p = 0.66; incidence of grade 3-5 adverse events: OR 0.78 [0.59-1.02], p = 0.73). Network estimates displayed 7 types of bevacizumab biosimilars in the medication regime of NSCLC patients who had no significant difference among each other in terms of efficacy and safety. The certainty of the evidence was assessed as low to moderate. Three types of biosimilars were found to be clinically equivalent to each other in the patients with CRC, which were evaluated with very low to moderate certainty.Conclusion: In patients with advanced NSCLC or metastatic CRC, the efficacy and safety of bevacizumab biosimilars were found to be comparable with those of reference biologics and each other.